'Psychoanalysis is one more way of taking people seriously': Adam Phillips in conversation with Emma Williams. Issue 1 (27th April 2022) - Phillips, Adam; Williams, Emma
Abstract: Adam Phillips is a leading psychoanalyst and author. Phillips was educated at Clifton College and studied English Literature at Oxford University. He trained to be a psychoanalyst at the Institute of Child Psychology. Across the course of his professional career, he has worked at Guys Hospital, with a school for 'maladjusted children', at Camberwell Child Guidance Clinic and at Charing Cross Hospital in the Department of Child Psychiatry. He now works in private practice. Phillips is the author of many works, including Terrors and Experts (1997), In Writing: Essays on Literature (2016), Attention Seeking (2019) and his most recent book, The Cure for Psychoanalysis (2021). He also served as the General Editor of the New Penguin Classics Translations of the works of Sigmund Freud. The conversation begins by exploring the way mental health has become a topic of public interest as a result of the COVID‐19 pandemic. The opportunities and challenges in Phillips's experience working with schools and for young people's mental health services during the 1970s, 1980s and 1990s are then discussed. Questions about the nature of psychoanalysis are introduced, and the discussion turns towards the relationship between philosophy, literature and psychoanalysis. There is a brief discussion of connections between Phillips's work and the philosophy of Stanley Cavell. Phillips's essays on schools and education are explored in connection with ideas of omniscience, sadomasochism and 'experiments in living'. The conversation ends with a glimpse of school as a place to cultivate one's interest and one's sociability with others.